Enzyme-responsive vitamin D-based micelles for paclitaxel-controlled delivery and synergistic pancreatic cancer therapy - Diana Peixoto; João M. Ravasco; Barbara Blanco-Fernandez; Francisco Veiga; Angel Concheiro; João Conde; Ana Cláudia Paiva-Santos; Carmen Alvarez-Lorenzo (Materials Today Bio)
Pancreatic ductal adenocarcinoma (PDAC) remains one of the most feared diseases worldwide owing to its poor prognosis, negligible therapeutic advances, and high mortality. Herein, multifunctional enzyme-responsive micelles for the controlled delivery of paclitaxel (PTX) were prepared to circumvent its current clinical challenges. Accordingly, two enzyme-responsive structural units composed of Vitamin D3 (VD3) conjugated with polyethylene glycol of different molecular weights (600 Da and 2000 Da) were synthesized and characterized using different analytical methods. By applying the solvent evaporation method, these bioactive structural units self-assembled into sub-100 nm VD3 micelles with minimal batch-to-batch variation, monomodal particle size distribution, and high encapsulation efficiency. The enzyme-triggered disassembly of PTX-loaded VD3 micelles was demonstrated by release studies in the presence of a high esterase content typically featured by PDAC cells. PTX-loaded VD3 micelles also exhibited prominent cell internalization and induced a considerable cytotoxic synergistic effect against human PDAC cells (BxPC-3 cells) in 2D and 3D cell culture models compared with free PTX. The PTX-loaded VD3 micelles were hemocompatible and stable after long-term storage in the presence of biorelevant media, and showed higher efficiency to inhibit the tumor growth compared to the approved clinical nanoformulation (Abraxane®) in an in ovo tumor model. The findings reported here indicate that VD3S-PEG micelles may have a promising role in PDAC therapy, since VD3 could act not only as a hydrophobic core of the micelles but also as a therapeutic agent that provides synergetic therapeutic effects with the encapsulated PTX.